Nicotinamide Mononucleotide Alleviates LPS-Induced Inflammation and Oxidative Stress via Decreasing COX-2 Expression in Macrophages - Liu, Jing; Zong, Zhaoyun; Zhang, Wenhao; Chen, Yuling; Wang, Xueying; Shen, Jie; Yang, Changmei; Liu, Xiaohui; Deng, Haiteng (Frontiers in Molecular Biosciences, 2021)
Macrophage activation is an important process in controlling infection, but persistent macrophage activation leads to chronic inflammation and diseases, such as tumor progression, insulin resistance and atherosclerosis. Characterizing metabolic signatures of macrophage activation is important for developing new approaches for macrophage inactivation. Herein, we performed metabolomic analysis on lipopolysaccharide (LPS)-activated macrophages and identified the associated changes in metabolites. Notably, the cellular NAD+ levels were decreased while NADPH was increased, proposing that NAD+ restoration can inhibit macrophage activation. Indeed, supplementation of nicotinamide mononucleotide (NMN) increased cellular NAD+ levels and decreased cytokine productions in LPS-activated cells. Quantitative proteomics identified that NMN downregulated the expressions of LPS-responsive proteins, in which cyclooxygenase-2 (COX-2) expression was significantly decreased in NMN-treated cells. Consequently, the cellular levels of prostaglandin E2 (PGE2) was also decreased, indicating that NMN inactivated macrophages via COX-2-PGE2 pathway, which was validated in activated THP-1 cells and mouse peritoneal macrophages. In conclusion, the present study identified the metabolic characteristics of activated macrophages and revealed that NMN replenishment is an efficient approach for controlling macrophage activation.